The effect of signal distortion techniques for PAPR reduction on the BER performance of coded OFDM systems in AWGN and Rayleigh fading channels - Soriano, Referendo D. (2005)
This study investigates the effect of signal distortion techniques on the Bit Error Rate (BER) performance of Coded Orthogonal Frequency Division Multiplexing (COFDM) communication systems. The signal distortion techniques include peak windowing and clipping, which are used to address the high Peak-to-Average Power Ration (PAPR) characteristics of OFDM signals. Computer simulations are used to quantify subsequent degradation of the BER of a COFDM system with two error control codes, namely Turbo and low Density Parity Check (LDPC) coes, upon the application of the PAPR reducing signal distortion techniques mentioned. The COFDM system is simulated in an additive white Gaussian noise (AWGN) and exponentially decaying Rayleigh fade channels. It is found that Low Density Parity Check coded OFDM (LDPC-COFDM) performs better than the Turbo coded OFDM (T-COFDM) on the channel models mentioned. Upon the application of signal distortion techniques, reduction in the coding gain was experienced by the LDPC-COFDM and T-COFDM. Peak windowing gives greater performance degradation among the signal distortions. However, only a minimal loss of about 1.2 dB in an AWGN and 0.0 dB in an application of peak windowing. While the LDPC-COFDM system experienced a performance degradation of about 4.1 dB and 1.2 dB in an AWGN and exponentially decaying Rayleigh fade channel, respectively. Thus, the effect of signal distortion to the T-COFDM performance is a good trade off, considering a reduction of 6.51 dB from a 9.77 dB PAPR level to 3.26 dB.
CD contains MATLAB codes.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Signal processing; Phase distortion (Electronics).; Multiplexing; Wavelength division multiplexing